Assessing the impact of FFP3 masks to oxygen saturation and pulse rate in the Oral Surgery department at the Glasgow Dental Hospital during the COVID‐19 pandemic: an observational study. (11th July 2021) - Rehman, Ilyaas; Ali, Sarah; O'Brien, Conor; Goodall, Christine
Abstract: Aim: The impact on physiological parameters and well‐being from potential respiratory distress caused by FFP3 masks, particularly during extensive clinical sessions, has been widely speculated during the COVID‐19 pandemic. This study aims to investigate the effect of FFP3 mask wear on clinicians' pulse rate and oxygen saturation. Material & Methods: Clinical staff within the Oral Surgery department recorded their oxygen saturation (SpO2) and pulse rate prior to donning an FFP3 mask, prior to doffing FFP3 mask and after doffing FFP3 mask using a finger pulse oximeter for a two‐week period in May–June 2020. The duration of wear, the session (AM/PM), the brand of mask and the presence of previous COVID‐19 symptoms were also recorded. Results: Twenty‐eight data sets were collected from twelve participants (1M:11F). Of the FFP3 masks worn, nineteen (67.86%) were ARCO TM, eight (28.57%) were 3M TM masks and one (3.57%) was 3M+ TM . At baseline, the mean SpO2 was 98.39% and the mean pulse rate was 72.11. Prior to mask removal, the mean SpO2 was 97.82% and the mean pulse rate was 70.04. At the end of the session, the mean SpO2 was 98.14% and the mean pulse rate was 69.54. The mean duration of wear was 150.34 min. Data sets were collected evenly across AM (14) and PM (14) sessions. Five participants (17.86%) reported previous COVID‐19 symptoms. Conclusion: The data demonstrated a mean reduction of 0.25% in oxygen saturation and 3.56% in pulse rate, following the use of an FFP3 mask. These changes in physiological parameters are not clinically significant and sessional use appears to be safe.